THE BEHAVIOUR OF HOUSEHOLDS TOWARDS ELECTRICITY CONSUMPTION: A CASE STUDY AT SEREMBAN - Kasavan, Saraswathy; Sharif Ali, Sharif Shofirun; Siron, Rusinah (PLANNING MALAYSIA, 2021)
Understanding energy consumption behaviours among households is an effective way to encourage energy conservation and improve energy efficiency. This article examines households’ knowledge, awareness, commitment, attitude, and behaviour towards electricity consumption. The sample of the study consists of 360 urban households in an intermediate city, Seremban. The findings reveal that cost-saving via government initiatives is a crucial factor influencing the households’ energy consumption knowledge. The correlation analysis also revealed that knowledge, awareness, commitment, and attitude correlated significantly with the households’ electricity consumption behaviour. The evidence suggests that the government and power companies implement strict regulations and technological advances to promote energy conservation and improve energy efficiency among households. The findings can better understand where attention should be directed and the measures for long-term energy conservation, climate change mitigation, and sustainable development.